2021
DOI: 10.1115/1.4050129
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Four-Dimensional Computed Tomography as a Technique for Quantifying Carpal Motion

Abstract: Delayed diagnosis of dynamic carpal instability often occurs because early changes in bone alignment and movement are difficult to detect and manifest mainly during a dynamic/functional task. Current diagnostic tools are only able to examine the carpal bones under static or sequential-static conditions. Four-dimensional (three dimensions + time) computed tomography (4DCT) enables quantification of carpal mechanics through 3D volume sequences of the wrist in motion. A comprehensive understanding of carpal mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…13 4DCT or quasi-dynamic CT has been used to assess SL biomechanics in uninjured participants, those with SL injuries preoperatively, and in cadaveric studies of SL biomechanics. 24,[27][28][29][30][31][32][33][34]51 This work builds on previous studies to demonstrate the applicability of 4DCT as a diagnostic and evaluation tool to reveal arthrokinematic changes at the radioscaphoid joint and SL intervals. While studies have evaluated the diagnostic utility of 4DCT, 31,52 this work highlights its role in postsurgical evaluation, especially in discerning subtle arthrokinematic changes.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…13 4DCT or quasi-dynamic CT has been used to assess SL biomechanics in uninjured participants, those with SL injuries preoperatively, and in cadaveric studies of SL biomechanics. 24,[27][28][29][30][31][32][33][34]51 This work builds on previous studies to demonstrate the applicability of 4DCT as a diagnostic and evaluation tool to reveal arthrokinematic changes at the radioscaphoid joint and SL intervals. While studies have evaluated the diagnostic utility of 4DCT, 31,52 this work highlights its role in postsurgical evaluation, especially in discerning subtle arthrokinematic changes.…”
Section: Discussionmentioning
confidence: 64%
“…Over the past decade, four-dimensional CT (4DCT)—standard 3DCT captured over motion cycles—has been introduced to capture CT volumes at evenly spaced time points during wrist motion with high spatial and temporal resolution. 24 25 26 27 28 29 30 31 32 33 34 35 This may allow identification of early ligamentous injuries and influence treatment strategy. 24…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic CT provides 3D images over time, allowing for more accurate estimates of hand joint kinematics than is possible with motion capture systems. Several recent studies have utilized dynamic CT for various musculoskeletal applications and have demonstrated the feasibility of dynamic CT imaging for measuring joint motion (i.e., rotations and translations), displacements, and even estimates of joint contact [10][11][12][13][14]. However, post-processing methods for dynamic CT datasets published to date are time intensive, reducing the practicality of applying this technique to larger clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in this field used distance mapping to illustrate distances between the scaphoid and the lunate [ 13 , 14 ]. Recently, Robinson et al used colour-coded distance mapping as joint congruency maps of the radioscaphoid and scapholunate joint in extreme radial and ulnar deviation to illustrate the contact areas in the joint during motion using 4D-CT [ 15 ].…”
Section: Introductionmentioning
confidence: 99%